MEDICAL STATISTICS OF WOMEN'S HEALTH AND FAMILY PLANNING - Fakhrurrazi Santoso (Mount Hope Economic Global Journal, 2024)
It is hoped that from this discussion We as student especially We in the midwifery know problem any statistics Medical Women's Health And Planning Family ?. This research did study descriptive with approach qualitative . Research result that is leave from Problem The population in Indonesia is divided into two , namely related demographics with physical / quantitative and non- demographic which is more in the direction qualitative . Outline happen significant decrease to level growth population , number death babies , and the number of poor people. There are various programs for reduce various problem population should become attention all related parties for improvement continued quality of human resources happen . Apart from that, the government should notice return existing policies and legislation made To use welfare of the Indonesian people.